2022
DOI: 10.7759/cureus.25768
|View full text |Cite
|
Sign up to set email alerts
|

Long-Lasting Efficacy of Radio Electric Asymmetric Conveyer Neuromodulation Treatment on Functional Dysmetria, an Adaptive Motor Behavior

Abstract: Background Fluctuating asymmetry (FA) is widely defined as the deviation from perfect bilateral symmetry and is considered an epigenetic measure of environmental stress. Rinaldi and Fontani hypothesized that the FA morpho-functional changes originate from an adaptive motor behavior determined by functional alterations in the cerebellum and neural circuits, not caused by a lesion, but induced by environmental stress. They called this phenomenon functional dysmetria (FD). On this premise, they develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 38 publications
(53 reference statements)
0
26
0
Order By: Relevance
“…It is a preprogrammed single session treatment, and it is administered by applying the tip of the metallic REAC asymmetric conveyer probe (ACP) to a specific area of the ear, according to the NPO protocol. Previous studies have shown that NPO treatment is able to induce an overall reorganization of postural and motor controls (Fontani et al, 2022 ; Mura et al, 2012 ; Rinaldi et al, 2014 ). This capacity of the NPO treatment was proved even in neurodegenerative diseases such as Parkinson’s (Fontani et al, 2012a , 2012b ) and Alzheimer’s (Olazaran et al, 2013 , 2014 ).…”
Section: Methodsmentioning
confidence: 96%
“…It is a preprogrammed single session treatment, and it is administered by applying the tip of the metallic REAC asymmetric conveyer probe (ACP) to a specific area of the ear, according to the NPO protocol. Previous studies have shown that NPO treatment is able to induce an overall reorganization of postural and motor controls (Fontani et al, 2022 ; Mura et al, 2012 ; Rinaldi et al, 2014 ). This capacity of the NPO treatment was proved even in neurodegenerative diseases such as Parkinson’s (Fontani et al, 2012a , 2012b ) and Alzheimer’s (Olazaran et al, 2013 , 2014 ).…”
Section: Methodsmentioning
confidence: 96%
“…At the time of our first observation, functional limitation at the proximal level of the right upper limb did not allow the arm to be raised and compromised accustomed movements such as drinking or bringing food to the mouth. The patient was also examined for the presence of functional dysmetria [ 10 , 11 , 15 ] (FD), which manifests itself as an asymmetrical activation of symmetrical muscle groups, in our case at the level of the quadriceps femoris. FD can be related to acquired disorganization of the neuro-psycho-motor control in relation to the allostatic load [ 16 , 17 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…In the case described in this study, to try to modulate the dysfunctional neuro psycho motor behavior (DNPMB) that can aggravate the clinical picture of the FAS, we used three noninvasive and specific neuromodulation treatments of the Radio Electric Asymmetric Conveyer (REAC) technology. The first is called Neuro Postural Optimization (NPO) with the aim of functionally reorganizing the functional cerebrum -cerebellum activity and improving motor control [10][11][12]. The second is called Neuro Psycho Physical Optimization (NPPO), and the third is called Neuro Psycho Physical Optimization Cervico-Brachial (NPPO-CB) with the aim of improving the state of depression, anxiety, and stress [13,14], which can negatively affect the clinical picture.…”
Section: Introductionmentioning
confidence: 99%
“…To accomplish this, it generates an asymmetrical activation of symmetrical muscle groups. This phenomenon has been termed functional dysmetria (FD) [ 3 , 4 ] and is detectable even in healthy subjects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%